Evaluation of the Presidential System of Government in Indonesia from a Theoretical and Practical Perspective - Triana, Herdi; Miswan (Social Impact Journal, 2025)
The system of government is the fundamental structure in state administration that determines the direction of power management, the relationship between state institutions, and the form of interaction between the government and the people. Constitutionally, Indonesia adheres to a presidential system of government as stated in the 1945 Constitution. However, in practice, this system has undergone adjustments and influences from the parliamentary system, resulting in a unique and distinctive model of governance. This study aims to analyze the characteristics of the presidential system in Indonesia, evaluate its strengths and weaknesses, and examine the dynamics of transformation and adaptation of the system within the socio-political context of Indonesia. This research uses a descriptive qualitative approach based on literature review by analyzing academic literature, scientific journals, constitutional documents, as well as historical and legislative studies. The findings indicate that Indonesia’s presidential system offers strengths such as executive stability, strong legitimacy from voters, policy consistency, and clear separation of powers. However, it also has weaknesses including the potential for power concentration, difficulty in leadership transition, deadlocks between the executive and legislative branches, and lack of flexibility during crises. In practice, Indonesia's presidential system has undergone hybridization through the adoption of parliamentary elements, especially in the legislative oversight mechanisms over the president. Therefore, the presidential system in Indonesia cannot be understood as a rigid model, but rather as an evolving and adaptive system that aligns with the needs of democracy and national political realities. This study recommends the strengthening of checks and balances mechanisms as well as institutional reforms to ensure a more effective, democratic, and accountable system of governance.